Strategi Promosi Dan Personal Selling Dalam Meningkatkan Minat Beli Konsumen Pada Toko Jaya Ponsel - Vicky Brama Kumbara; Arifa Khairiza Azri; Aulia Citra; M Riski (CV. ITTC INDONESIA, 2024)
This report outlines the promotional and personal selling strategies implemented to increase consumer buying interest in Toko Jaya Ponsel. This Field Work Practice (PKL) was carried out by students majoring in Management, Faculty of Economics and Business, Universitas Putra Indonesia